2020
DOI: 10.1111/jphd.12397
|View full text |Cite
|
Sign up to set email alerts
|

The integration of oral health‐related best practice recommendations in the management of patients with diabetes: a cross‐sectional survey of primary care physicians

Abstract: ObjectiveTo determine whether best practice recommendations are being followed by primary care physicians (PCPs) by examining the integration of oral health‐related practices in their management of patients with diabetes.MethodsA cross‐sectional study design was used to examine PCPs' knowledge of the bidirectional link between diabetes and periodontal disease (PD), their adherence to international best practice recommendations, and their experience of interprofessional collaboration with dentists via an online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…[16][17][18][19] It has been demonstrated that IPE advances collaborative practice, reduces medical errors, and enhances health outcomes of patients and populations. [20][21][22][23][24] The Association of American Medical Colleges (AAMC) advocated for oral health education for medical students and now expects medical students to demonstrate competence in multiple domains within oral health, such as understanding the caries and periodontal disease process and its implications for systemic health, performing oral health screenings, promoting preventive strategies, and collaborating with dental professionals. 25 The National Call to Action to Promote Oral Health called for revamping health professions education to include oral health content as a key step towards eliminating oral health disparities.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] It has been demonstrated that IPE advances collaborative practice, reduces medical errors, and enhances health outcomes of patients and populations. [20][21][22][23][24] The Association of American Medical Colleges (AAMC) advocated for oral health education for medical students and now expects medical students to demonstrate competence in multiple domains within oral health, such as understanding the caries and periodontal disease process and its implications for systemic health, performing oral health screenings, promoting preventive strategies, and collaborating with dental professionals. 25 The National Call to Action to Promote Oral Health called for revamping health professions education to include oral health content as a key step towards eliminating oral health disparities.…”
Section: Introductionmentioning
confidence: 99%
“…As GPs may be involved in oral health care in primary care settings, improving oral health training of GP may in turn improve GPs engagement in the management of oral conditions. Currently, there has been limited culture of collaborative practice between GPs and dental practitioners, which is essential in effectively mitigate oral health disparities [ 20 , 59 ]. Despite evidence suggesting integrated healthcare model incorporating dental practitioners into primary care may lower overall healthcare cost[ 60 ], dental practitioners are frequently not included as a part of the healthcare team in primary care settings [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, focusing on oral health in diabetics is sometimes considered of lower importance compared to other diabetic complications. General practitioners thus rarely inform their patients with DM about the association of their main disease and periodontal disease ( 14 ).…”
Section: Introductionmentioning
confidence: 99%